1998
DOI: 10.1016/s0895-7061(98)00154-x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral nephrectomy: the best, but often overlooked, treatment for refractory hypertension in hemodialysis patients

Abstract: Bilateral nephrectomy for treatment of refractory hypertension in chronic hemodialyzed patients has been infrequently carried out. We analyzed the benefits of this operation on blood pressure, clinical state, drug treatment, and quality of life. In 10 hemodialyzed patients with refractory hypertension, systolic (SBP) and diastolic (DBP) blood pressure were measured 1 month before nephrectomy bilateral and 3, 6, 9, and 12 months after. In addition, the use of antihypertensive drugs before and after surgery was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Similar sympathoinhibitory effects of nephrectomy were observed in renal transplant recipients [6]. Furthermore, bilateral nephrectomy leads to strikingly improved blood pressure control in hemodialysis patients with refractory hypertension [29].…”
Section: Discussionsupporting
confidence: 53%
“…Similar sympathoinhibitory effects of nephrectomy were observed in renal transplant recipients [6]. Furthermore, bilateral nephrectomy leads to strikingly improved blood pressure control in hemodialysis patients with refractory hypertension [29].…”
Section: Discussionsupporting
confidence: 53%
“…Zazgornik et al. [4] analysed the benefits of bilateral nephrectomy in 10 patients (four with malignant hypertension) and reported that the blood pressure improved significantly in all patients and became normal in nine. In a recent study, Power et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, refractory hypertension poorly controlled with drugs is occasionally seen. In this subset of patients, BPN has been recommended [2][3][4][5]. Open BPN was associated with high morbidity and mortality, as reported in some of earlier series [6,7], with values of 3.6-4% and 18-40%, respectively, in 1970s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with resistant and refractory HTN are at risk of significant comorbid conditions, as one study showed that patients with resistant hypertension have a 32% increase in the risk of developing ESRD, a 24% increase in the risk of myocardial ischemia, a 46% increase in the risk of heart failure, a 14% increased risk of cerebrovascular events, and a 6% increased risk of mortality. Patients with chronic kidney disease are at risk of developing HTN, resistant HTN, and refractory HTN secondary to volume overload, sympathetic overactivity, activation of the renin-angiotensin system, and arteriosclerosis, with a prevalence of 50%-60% of ESRD patients on hemodialysis being hypertensive, and a prevalence of resistant hypertension of 33.4%, 28.9%, and 15.8% in chronic kidney disease with estimated glomerular filtration rate (eGFR) levels of <45 ml/min, 45-60 ml/min, >60 ml/min, respectively [1,[3][4].…”
Section: Discussionmentioning
confidence: 99%